Study of Heterocyclic Ring Systems: Biopharmaceutical Applications of Substituted 4H-1, 4-Benzothiazine and Piperazine. (May 2020) - Saroha, Sumit; Chhavi,; Sharma, Praveen Kumar
Abstract: In present work study of biologically important heterocycles such as 4H-1, 4-benzothzine and substituted piperazine was carried out. Reaction mixture of substituted 4H-1, 4-Benzothiazine and piperazine was examined for their importance as biopharmaceutical material such as antimicrobial and antioxidant agents. Current research article based on fundamental concept of green chemistry best out of waste.